A few observations about the links between Lithuanian Calvinist texts and Prussian Lithuania - Kabašinskaitė, Birutė (Vilnius University Open Series, 2022)
This article continues the research of the 19th-century Lithuanian Calvinist texts. A hypothesis was raised regarding the unusual structure of Mykolas Cerauskas Seanas katechismas (1803), i.e. the sequence of parts of the catechesis. This sequence could have been determined by the 18th-century catechism compiler (whose work was taken over by Cerauskas) relying on the first catechism of Jan Seklucjan, published in East Prussia, or perhaps the traditional structure of early German catechisms (the works of Georg Major), which was closely related to the education of children in the late Middle Ages. Another Calvinist work is even more closely related to Prussian Lithuania and children’s education – the primer ABC knigeła (1861). It was detected that it was not an original work, but a text (a small fragment) taken from Friedrich Kurschat’s (1841) publication of the translation of the catechism and its comments prepared by Johann Gottlieb Weiß. The primer cannot be considered solely borrowed from the Prussian Lithuanian Lutheran writings, because the Calvinist editor made numerous spelling and lexical corrections, which brought it very close to the Calvinist writing tradition. In the middle of the 19th century, there were more Calvinist publications, whose authors included the texts of the Lutherans of Prussian Lithuania that were rearranged in their own way.
Keywords: Lithuanian Calvinist writings; Prussian Lithuanian writings; catechism; sequence of catechesis parts; primer; text editing; Mykolas Cerauskas; Michał Ceraski; Friedrich Kurschat; Kuršaitis